Audiovisual aids as a resource to enhance speaking skill among 8th year students of basic education, at “18 de November” school of Loja city, during the academic period 2014 – 2015 - Gonzaga Camizan, Santiago (2016)
This research work has been developed with the purpose of enhance students‘ speaking skills on eighth year at 18 de Noviembre school through the use of audiovisual aids as a resource. The methods used were: the scientific, analytical, synthetic, statistical and the descriptive which help to analyze and supported the information gathered. The main instruments applied to thirty – eight students were, tests and questionnaires. Furthermore, observation sheets and field diaries were used. The information obtained from the instruments were presented in tables and figures. The main results of the research work were that students showed a considerable improvement in their speaking skills in the aspects of vocabulary, accuracy, task completion, and speaking mechanics. It is concluded that the application of the audiovisual aids was successful, since, students at the end of the intervention increased their level of participation, performance and cooperation in the English classes.